Extraction, bioevaluation and characterization of soybean and locust bean seeds proteins as plant-based meat substitutes - Sadiya Alka; Halima Bawa; Muhammad Jamilu Dauda; Sulaiman Mohammed; Ahmed Olatunde; Jamila Salihu; Khadija Aliyu Nuru; Misbahu Abdullahi Tahir; Eloanyi Sylvester Ikenna; Akinwoye Rukayat Oyefunke (Regulatory Toxicology and Pharmacology, 2026)

Exploring the epidemiology of Newcastle disease in Northern Nigeria: A mixed approach - Mayowa Peter Olabode; Usman Adamu Rayyanu; Victoria Isioma Ifende; Ismaila Shittu; Rebecca Paul Weka; Isabella Monne; Matthew Yakop Gukut; Ladi Amos Chabiri; Yakubu Joel Atuman; Judith Dizot Bakam; Falmata Haruna Bwala; Zenaba Mahamat Kodo; et al. (Preventive Veterinary Medicine, 2026)

Climate-resilient livestock systems in Sub-Saharan Africa: a one health systems framework integrating pastoralism, animal health, and sustainable development - Muhammad Yasir Alhassan; Abdulhamid Abdullahi Ahmad; Mubarak Aliyu Danmaraya (Tropical Animal Health and Production, 2026)

Multiscale spatiotemporal analysis and predictability of long-term meteorological drought in the Kaduna river basin (1901–2024) - Muhammad Lawal Abubakar; Saadatu Umaru Baba; Sidikatu Aliyu; Habiba Ibrahim Mohammed; Hindatu Abdulkadir; Muhammad Sambo Ahmed; Madinatu Ahmad; Auwal F. Abdussalam (Theoretical and Applied Climatology, 2026)

Digital twin-centered food safety management systems: A review of IoT, AI, and blockchain integration for bacterial pathogen control - Balarabe B. Ismail; Abdulrazaq Hassan Abba; Abdulrashid Ibrahim Sanka; Aliyu Idris Muhammad; Wenjun Wang; Donghong Liu (Food Research International, 2026)

Enhancing microbial safety and enzymatic stability of green peas using sequential sodium hypochlorite washing and continuous in-package DBD plasma treatment - Aliyu Idris Muhammad; Marlenne X. Atta-Delgado; Feihong Ji; Kevin M. Keener; Tian Ding; Xinyu Liao (Food Research International, 2026)

Spatiotemporal Assessment of Agricultural Drought in Semiarid Northern Nigeria Using MODIS Data and Explainable Random Forest (2000–2025) - Muhammad Lawal Abubakar; Asmau M. Ahmed; Sidikatu Aliyu; Saadatu Umaru Baba; Muhammad Sambo Ahmed; Khalid Ibrahim Richifa (Pure and Applied Geophysics, 2026)

Widespread Use of Banned Pesticides and Weak Regulatory Enforcement: Environmental and Health Implications Among Farmers in Gombe State, Nigeria - Mohammad Bashir Sulaiman; Babangida Hammani; Abdullahi Muhammad Gimba; Oluyinka Omoyeni Akinlotan; Aliyu Tijjani Fadawa; Umar Musa Kwami; Taibatu Idris Umar; Amina Muhammad Bello (Journal of Agromedicine, 2026)

Valorization of rubber waste for the synthesis of an acidic heterogeneous catalyst for efficient palm fatty acid distillate esterification - Muhammad Aliyu; Junaid Ahmad; Chawalit Ngamcharussrivichai; Kamil Kayode Katibi; Syed Ahmar Ali Hashmi; Umer Rashid (Process Safety and Environmental Protection, 2026)

Preparation, characterization and flocculation performance of fungi-nanoparticle conjugates for efficient harvest of Chlorella vulgaris - Muhammad Hizbullahi Usman; Abdulrahman Sahabi; Muhammad Bello; Aliyu Ibrahim Dabai (Bioresource Technology Reports, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Culturing freshwater crayfish (Cherax quadricarinatus) in a static biofloc culture system based on fruit-wastes: Effects on growth, nutrient composition and bioeconomics - Muhammad Aliyu Sulaiman; Yih Nin Lee; SM Nurul Amin; Lirong Yu Abit; Sabarinath Rangiem Narayanan; Ravi Fotedar (Aquacultural Engineering, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Spatial analysis of domestic energy deprivation in Minna, Nigeria - Chukwudi Bernhard Ohadugha; Lilian Chioma Obi-George; Aliyu Yaman Muhammad; Saheed Adeyemi Adegoke; Oluchi Chinenye Ifebi; Maryann Nkechi Maduka (Energy and Buildings, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

When farmers’ knowledge matters: Improving epidemiological understanding of Peste des petits ruminants in northern Nigeria - Zenaba MAHAMAT KODO; Usman Adamu RAYYANU; Mayowa Peter OLABODE; Victoria Isioma IFENDE; Rebecca Paul WEKA; Matthew Yakop GUKUT; Alexis DELABOUGLISE; Ismaila SHITTU; Yakubu Joel ATUMAN; Judith Dizot BAKAM; Falmata Haruna BWALA; Ladi Amos CHABIRI; et al. (Preventive Veterinary Medicine, 2025)

Insect-based biofuels and animal feed additives: A sustainable energy and agricultural solution for Africa's future - Abdulbariu Ogirima Uhuami; Hadiza Aliyu; Badiat Jamila Danjumma; Saadatu Mohammed Bawa; Aminu Muhammad Lawal; Shamsudeen Umar Dandare; Aliyu Ibrahim Dabai (Next Research, 2025)

Immuno-nutritional therapy in experimental autoimmune encephalomyelitis: a translational pathway to multiple sclerosis management - Mansur Aliyu; Ali Akbar Saboor-Yaraghi; Muhammad Ibrahim Getso; Fatema Tuz Zohora (Inflammopharmacology, 2025)

Geostatistical and multivariate analysis of phosphate evolution and its relationship with heavy metals in shallow groundwater in a Semi-Arid Basin - Saadu Umar Wali; Noraliani Binti Alias; Abdulqadir Abubakar Usman; Abdullahi Umar; Nasiru Muhammad; Ismail Usman Kaoje; Buhari Samaila; Basiru Aliyu; Habiba Muhammad Ladan; Mudassiru Atiku; Sa’ad Ibrahim (Earth Science Informatics, 2025)

Enhancement on optical properties and radiation shielding performance of new formulation zinc modified boro-tellurite glasses - Aliyu Sani; Mohd Hafiz Mohd Zaid; Khamirul Amin Matori; Muhammad Khalis Abdul Karim; Loh Zhi Wei (Annals of Nuclear Energy, 2025)

Pharmacological Potential of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835): Antibacterial Activity Against Methicillin-Resistant Staphylococcus aureus and Metabolite Profile - Abdoulie Ceesay; Muhammad Farhan Nazarudin; Norfarrah Mohamed Alipiah; Ina Salwany Md Yasin; Mohammad Noor Azmai Amal; Mohamad Azzam Mohd Sayuti; Intan Safinar Ismail; Mohammed Aliyu-Paiko (Thalassas: An International Journal of Marine Sciences, 2025)

Performance of geothermal energy piles in buildings: A bibliometric analysis and systematic review - Muhammad Abubakar Baffa; Zahiraniza Mustaffa; Niraku Rosmawati Ahmad; Mohamed E. El-Atroush; Nura Shehu Aliyu Yaro; Mohamed El Amine Ben Seghier (Energy and Buildings, 2025)

Assessment of Fruit Waste as Feed Additives in Aquafeed for Growth Performance and Health Benefits of Fishes Under Biofloc Technology - Muhammad Aliyu Sulaiman; Lee Yih Nin; S. M. Nurul Amin; Ravi Fotedar; Fatimah Md Yusoff; Julia Hwei Zhong Moh (Reviews in Aquaculture, 2025)
The rising demand for fish and crustacean products has placed significant pressure on traditional aquaculture practices, which are increasingly unsustainable. Utilizing fruit waste as a feed ingredient in biofloc systems presents a promising solution for enhancing the sustainability and cost‐efficiency of fish farming. Studies have demonstrated that the incorporation of fruit waste into aquafeed improves growth performance, feed utilization, and health outcomes in aquatic animals. This practice also addresses waste management issues and reduces dependency on conventional feed ingredients, which are becoming more expensive. However, factors such as the availability sustainability and scalability of fruit waste, remain important considerations. Research has shown that fish and crustacean fed diets supplemented with fruit waste exhibit superior growth, survival rates, and health compared to those on conventional diets. The highest weight gain and specific growth rates were observed in those fishes, with normal liver and intestinal histopathology. Additionally, fruit waste diets significantly enhanced hematological parameters, such as hemoglobin, red blood cells, and white blood cells, leading to improved immune responses and resilience during stress.

In-silico evaluation of Cassia occidentalis phytochemicals for Plasmodium falciparum plasmepsin V inhibition: Revealing antimalarial potential - Aliyu Usman Maaji; Ramgopal Dhakar; Pankaj Kumar Teli; Umesh Garu; Umar Aliyu Adamu; Saminu Saminu Muhammad; Khalipha Ali Jubril; Fatima Idris Sambo (South African Journal of Botany, 2025)

Improving Short-term Daily Streamflow Forecasting Using an Autoencoder Based CNN-LSTM Model - Umar Muhammad Mustapha Kumshe; Zakariya Muhammad Abdulhamid; Baba Ahmad Mala; Tasiu Muazu; Abdullahi Uwaisu Muhammad; Ousmane Sangary; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Mosaad Ali Hussein Ali; Aliyu Uthman Bello; Muhammad Muhammad Bala (Water Resources Management, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Bacillus spore germination: mechanisms, identification, and antibacterial strategies - Lihua Fan; Yanru Zhang; Balarabe Bilyaminu Ismail; Aliyu Idris Muhammad; Guoliang Li; Donghong Liu (Critical Reviews in Food Science and Nutrition, 2024)

Recycling polymeric healthcare waste in asphalt pavements towards sustainable roads: A technical review - Muhammad Sani Bello; Yuqing Zhang; Xingwang Wang; Nura Shehu Aliyu Yaro (Journal of Cleaner Production, 2024)

In silico analysis of balsaminol as anti-viral agents targeting SARS-CoV-2 main protease, spike receptor binding domain and papain-like protease receptors - Daniel Danladi Gaiya; Aliyu Muhammad; Joy Sim Musa; Richard Auta; Anthony John Dadah; Rachael Oluwafunmilayo Bello; Madinat Hassan; Samuel Sunday Eke; Rebecca Imoo Odihi; Musa Sankey (In Silico Pharmacology, 2024)

Waste Palm Leaves-Based Hydrochar Support Catalytic Esterification of Palm Fatty Acid Distillate - Muhammad Aliyu; Umer Rashid; Wan Azlina Wan Ab Karim Ghani; Mohamad Amran Mohd Salleh; Balkis Hazmi; Fahad A. Alharthi; Elsa Antunes; Jianglong Yu (BioEnergy Research, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Efficient production of biodiesel from palm fatty acid distillate using a novel hydrochar-based solid acid catalyst derived from palm leaf waste - Muhammad Aliyu; Bryan R. Moser; Fahad A. Alharthi; Umer Rashid (Process Safety and Environmental Protection, 2024)

Addressing knowledge gaps on emerging issues in weather and climate extreme events: a systematic review - Kamil Muhammad Kafi; Zakiah Ponrahono; Aliyu Salisu Barau (Climatic Change, 2024)

Analysis of land use and land cover change using machine learning algorithm in Yola North Local Government Area of Adamawa State, Nigeria - Auwal Aliyu; Muhammad Isma’il; Sule Muhammad Zubairu; Ibrahim Yahaya Gwio-kura; Abubakar Abdullahi; Babakaka Abdulsalam Abubakar; Muntaka Mansur (Environmental Monitoring and Assessment, 2023)

An autoencoder-based stacked LSTM transfer learning model for EC forecasting - Abdullahi Uwaisu Muhammad; Hamza Djigal; Tasiu Muazu; Jibril Muhammad Adam; Abdoul Fatakhou Ba; Umar Sani Dabai; Sani Tijjani; Muhammad Sabo Yahaya; Aliyu Ashiru; Umar Muhammad Mustapha Kumshe; Saddam Aliyu; Faruwa Ajibola Richard (Earth Science Informatics, 2023)

Cowpea landraces in northern Nigeria: overview of seedling drought tolerance - Solihu Kayode Sakariyahu; Sadam Sulaiman Indabo; Aminu Aliyu; Hadiza Usman Muhammad; Hauwa Oziohu Ahmed; Saba Baba Mohammed; Abu Kasim Adamu; Ramatu Enehezeyi Aliyu (Biologia, 2023)

A bioactive chalcone from the aerial parts of Indigofera conferta Gillet - Maryam Isah; Salima Murtala; Sakynah Musa Abdullahi; Asmau Nasiru Hamza; Nasir Tajuddeen; Mu’ammar Lawal Dauda; Vuyisa Mzozoyana; Aliyu Muhammad Musa (Natural Product Research, 2023)

Comparative mapping of smellscape clusters and associated air quality in Kano City, Nigeria: An analysis of public perception, hotspots, and inclusive decision support tool - Aliyu Salisu Barau; Kamil Muhammad Kafi; Mubina Auwal Mu'allim; Martin Dallimer; Abdulaziz Hassan (Sustainable Cities and Society, 2023)

Comparative cyto-genotoxicity and clastogenicity properties of traditional trypanocidal Afrormosia laxiflora and Lonchocarpus laxiflorus plants in Wistar rats - Lovina Chinyere Ogbu; Aliyu Muhammad; Mohammed Aliyu Usman; Musa Bashir; Abdullahi Balarabe Sallau (Toxicology and Environmental Health Sciences, 2023)

Dynamics of negotiated use of public open spaces between children and adults in an African city - Aliyu Salisu Barau; Ismaila Rimi Abubakar; Kamil Muhammad Kafi; Kemi Hamdat Olugbodi; Jibrin Ibrahim Abubakar (Land Use Policy, 2023)

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Effectiveness of emerging mechanisms for financing national climate actions; example of the Indonesia Climate Change Trust Fund - Muhammad Sheriffdeen; Dodik Ridho Nurrochmat; Perdinan; Hauwa Kulu Aliyu Abubakar (Climate and Development, 2023)

Corrigendum to ‘Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis’, Chemosphere, 311, (2023), 1–10, 137102 - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Effect of waste cooking oil on warm mix asphalt block pavement – A comprehensive review - Yusuf Babangida Attahiru; Azman Mohamed; Ahmed Eltwati; Aliyu Abubakar Burga; Abubakar Ibrahim; Abdullahi Muhammad Nabade (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Critical insight into sediment microbial fuel cell: Fundamentals, challenges, and perspectives as a barrier to black-odor water formation - Umar Abdulbaki Danhassan; Hongjian Lin; Ibrahim Lawan; Xin Zhang; Mahmoud H. Ali; Aliyu Idris Muhammad; Kuichuan Sheng (Journal of Environmental Chemical Engineering, 2023)

Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis. - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Assessment of Malaysian brown seaweed Padina gymnospora antioxidant properties and antimicrobial activity in different solvent extractions - Muhammad Farhan Nazarudin; Muhammad Syazwan Shahidan; Nur Amirah Izyan Noor Mazli; Tan Hui Teng; Yam Sim Khaw; Ina Salwany Md Yasin; Azizul Isha; Mohammed Aliyu-Paiko (Fisheries Science, 2022)

Physical Modelling of Offshore Wind Turbine Foundations for TRL (Technology Readiness Level) Studies - Subhamoy Bhattacharya; Domenico Lombardi; Sadra Amani; Muhammad Aleem; Ganga Prakhya; Sondipon Adhikari; Abdullahi Aliyu; Nicholas Alexander; Ying Wang; Liang Cui; Saleh Jalbi; Vikram Pakrashi; et al. (Journal of Marine Science and Engineering, 2021)
Offshore wind turbines are a complex, dynamically sensitive structure due to their irregular mass and stiffness distribution, and complexity of the loading conditions they need to withstand. There are other challenges in particular locations such as typhoons, hurricanes, earthquakes, sea-bed currents, and tsunami. Because offshore wind turbines have stringent Serviceability Limit State (SLS) requirements and need to be installed in variable and often complex ground conditions, their foundation design is challenging. Foundation design must be robust due to the enormous cost of retrofitting in a challenging environment should any problem occur during the design lifetime. Traditionally, engineers use conventional types of foundation systems, such as shallow gravity-based foundations (GBF), suction caissons, or slender piles or monopiles, based on prior experience with designing such foundations for the oil and gas industry. For offshore wind turbines, however, new types of foundations are being considered for which neither prior experience nor guidelines exist. One of the major challenges is to develop a method to de-risk the life cycle of offshore wind turbines in diverse metocean and geological conditions. The paper, therefore, has the following aims: (a) provide an overview of the complexities and the common SLS performance requirements for offshore wind turbine; (b) discuss the use of physical modelling for verification and validation of innovative design concepts, taking into account all possible angles to de-risk the project; and (c) provide examples of applications in scaled model tests.

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Bacterial spore inactivation induced by cold plasma - Xinyu Liao; Aliyu Idris Muhammad; Shiguo Chen; Yaqin Hu; Xingqian Ye; Donghong Liu; Tian Ding (Critical Reviews in Food Science and Nutrition, 2019)

5,6-dehydrokawain from the rhizome of Alpinia mutica Roxb. induced proangiogenic tumour-derived VEGF of HT-29 colorectal cancer - Ibrahim Malami; Aliyu Muhammad; Ibrahim B. Abubakar; Imaobong C. Etti; Peter M. Waziri; Ramadan M. Abubakar; Halilu E. Mshelia (Natural Product Research, 2018)

Effect of resveratrol and environmental enrichment on biomarkers of oxidative stress in young healthy mice - Mustapha Shehu Muhammad; Rabiu Abdussalam Magaji; Aliyu Mohammed; Ahmed-Sherif Isa; Mohammed Garba Magaji (Metabolic Brain Disease, 2017)

An efficient regeneration system and steviol glycoside analysis of Stevia rebaudiana Bertoni, a source of natural high-intensity sweetener - Buhara Yücesan; Refik Büyükgöçmen; Aliyu Mohammed; Muhammad Sameeullah; Cevher Altuğ; Songül Gürel; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

In vitro propagation and cardenolide profiling of Digitalis ferruginea subsp. schischkinii, a medicinally important foxglove species with limited distribution in Northern Turkey - Buhara Yücesan; Aliyu Mohammed; İsmail Eker; Muhammad Sameeullah; Öznur Demir-Ordu; Cansu Cihangir; Nevin Şahbaz; Özge Kaya; Frieder Müller-Uri; Wolfgang Kreis; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)

Exposure to mobile phone electromagnetic field radiation, ringtone and vibration affects anxiety-like behaviour and oxidative stress biomarkers in albino wistar rats - Abubakar Shehu; Aliyu Mohammed; Rabiu Abdussalam Magaji; Mustapha Shehu Muhammad (Metabolic Brain Disease, 2016)

Modulatory role of Acacia honey from north-west Nigeria on sodium arsenite-induced clastogenicity and oxidative stress in male Wistar rats - Aliyu Muhammad; Oyeronke A. Odunola; Michael A. Gbadegesin; Ayodeji M. Adegoke; J. Olorunjuwon Olugbami; Ndidi S. Uche (Natural Product Research, 2015)

Flavonoids with antimicrobial activity from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad Sani Sallau; Aliyu Muhammad Musa; Dama James Habila; Sani Muhammad Yahaya (Natural Product Research, 2014)